2010
DOI: 10.1007/s12185-010-0691-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PAX5 induces apoptosis in multiple myeloma cells

Abstract: PAX5 is an essential transcription factor for the commitment of lymphoid progenitors to the B-lymphocyte lineage. PAX5 suppression results in retrodifferentiation of B lymphocytes to an uncommitted progenitor cell stage, whereas PAX5 suppression in mature B lymphocytes leads to further development into plasma cells. Here, we have analyzed the fate of plasma cell lines following PAX5 reexpression. Human B cell lines were infected with Ad5/F35 adenoviruses encoding either EYFP or PAX5. Expression analysis of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
1
8
1
Order By: Relevance
“…Although overexpression of PAX5 has been reported to trigger nondrug-induced apoptosis in multiple myeloma cells (Proulx et al, 2010), our data suggest that PAX5 increases Bortezomib-induced NF-κB activation and drug-resistance by enhancing RIP2 Ser176 phosphorylation. Meanwhile, Bortezomib-induced apoptosis in primary multiple myeloma and leukemia cells has been proven to be related to PAX5 expression.…”
Section: Discussioncontrasting
confidence: 62%
“…Although overexpression of PAX5 has been reported to trigger nondrug-induced apoptosis in multiple myeloma cells (Proulx et al, 2010), our data suggest that PAX5 increases Bortezomib-induced NF-κB activation and drug-resistance by enhancing RIP2 Ser176 phosphorylation. Meanwhile, Bortezomib-induced apoptosis in primary multiple myeloma and leukemia cells has been proven to be related to PAX5 expression.…”
Section: Discussioncontrasting
confidence: 62%
“…In hepatocellular carcinoma PAX5 has been identified as a novel tumor suppressor through interacting with the p53 signaling pathway (Liu et al, 2011). Consistent with this, overexpression of PAX5 induces apoptosis in multiple myeloma cells (Proulx et al, 2010). PAX5 is expressed in medulloblastoma (Kozmik et al, 1995), and in a sub-type of neuroblastoma (Baumann Kubetzko et al, 2004), perhaps reflecting the earlier requirement for PAX5 expression in the mid/hindbrain boundary during embryogenesis (Urbanek et al, 1994).…”
Section: Pax5mentioning
confidence: 62%
“…The observation of interregulating capabilities between Pax-5 variants has also been made in murine models (23). A link between Pax-5 expression and apoptosis was also revealed in a study of multiple myeloma cell lines, in which the authors found that Pax-5 overexpression promoted apoptosis events (24). Other studies suggest a growth-inhibitory function for Pax-5.…”
Section: Pax-5 Functions In Oncogenic Processesmentioning
confidence: 80%